Willingness of students of professional education program​​ to join non permanent employee (PTT) - Diana, Jenny; Setiawan, Asty Samiaty; Yubiliana, Gilang (Padjadjaran Journal of Dentistry, 2012)
Introduction: Placement policy of doctors and midwives with PTT system has been implemented since 1992 to address the distribution of doctors and dentists who have not been evenly distributed in Indonesia, but until now its spread is still far from expected. The ratio of doctors in Puskesmas for the region in western Indonesia is much higher than eastern Indonesia. The purpose of this study was to determine the willingness of dental professional education program student of Faculty of Dentistry in Padjadjaran University to be non permanentemployee (PTT). Methodes: This study was a descriptive study done by survey technique. The data obtained by questionnaires. Results: Dental students of professional education programs who were willing to be a non permanent employee (PTT) was 82% and those who were not willing was 18%. Conclusion: The dental students of professional education programs mostly willing to be a non permanent employee.